Remote RF control for home appliance development board - Muhammad Zakuan, Ahmad Salim (2012)
Modern house nowadays are becoming more advance as many innovation inventions are invented in a fast rate as technologies are rapidly increasing. Some of the features for the control system for modern house are mail notification, power saving, water saving and smoke detection. An RF control system for modern house consists of two parts; transmitter and receiver. The transmitter is operated as a remote control and the receiver receive data from transmitter and then control the device. The system used wireless as the medium between remote control and controlled devices. This project is design for modern house to create the appliance control, efficient control and security system for modern house.